Lateral similarity and symmetry of biometric data from the LenStar in a population with cataract - Achim Langenbucher; Jascha Wendelstein; Alan Cayless; Stefan Wagenpfeil; Peter Hoffmann; David Cooke; Nóra Szentmáry (PLoS ONE, 2026)
Purpose To investigate the similarity and symmetry of biometric measures between eyes in a large dataset of measurements of both eyes taken with the LenStar optical biometer. Methods Cross-sectional non-randomised study evaluating a dataset containing 13,420 bilateral LenStar 900 biometric measurements on patients without history of eye surgery or ocular pathology taken before cataract surgery, consisting of scalar parameters axial length AL, corneal thickness CCT, anterior chamber depth ACD, lens thickness LT and corneal diameter WTW. The keratometric power vector components equivalent power KEQ were assessed for similarity, and the projections of corneal astigmatism vector KC0 and KC45 were analysed for direct and mirror symmetry with respect to the vertical (sagittal) plane. Results Mean / standard deviation (squared correlation coefficient) difference between right and left eye measures was 0.02 ± 0.31(0.95) / 0.00 ± 0.01(0.93) / 0.00 ± 0.14(0.88) / −0.01 ± 0.22(0.78) / −0.02 ± 0.17(0.87) mm for AL / CCT / ACD / LT / WTW and −0.06 ± 0.48(0.92) dioptres for KEQ. Keratometric astigmatism showed a high degree of mirror symmetry (KC45 of left eyes inverted in sign) which outperforms direct symmetry. The median deviation of the keratometric axes of both eyes considering mirror symmetry was 15 degrees compared to 29 degrees for direct symmetry. Conclusions In most cases, biometric measures match between eyes of a subject, but there are rare situations with large deviations between eyes. Keratometric astigmatism exhibits mirror symmetry. In most cases the biometric measures from the contralateral eye could be used where biometry is unavailable or to double-check before cataract surgery.